PROFESSIONAL PRESS OF PUBLISHERS: CONCEPTION AND DEVELOPMENT TRENDS IN LITHUANIA - BUIVYDIENĖ, ERIKA; ZINKEVIČIENĖ, JULIJA (Knygotyra, 2015)
Differently from great Western European countries, the professional press of Lithuanian publishers appeared at a rather late stage – in the early 20th century. Until that time, no transparent and clear traditions had been formed. Furthermore, even nowadays Lithuanian specialists of publishing have no periodicals that would satisfy the ir professional and informational needs. Therefore, the purpose of this article is to analyse the professional press from the historical point of view and to evaluate the current demand of these specialists in professional information. The study focuses on the following issues: the understanding and concept of professional press, retroactive description of the professional press of publishers in Lithuania, comparison of the development stages with the professional press of publishers in Western European countries, evaluation of the current status of the professional press of publishers in Lithuania.Presumably, the professional periodicals of publishers have not been subject to analysis in Lithuania. Thus, using the method of scientific analysis of literature, the author of study analyses the concept of professional press, the definitions of the key terms, makes a typological analysis of periodicals. By the historical method, the analysis deals with the conditions of appearance of professional periodicals and their development stages; the causalities and consistent patterns are defined. The historical research of the professional periodical press of Lithuanian publishers revealed that the low demand and popularity of professional press were caused by the relatively small circle of professionals in the field. Most of the professional periodicals published in the early 20th century were short-lived and often limited to issues of a few copies. Only the publications of advertising books, aimed at publishers and the educated part of the reading society survived for longer periods, meanwhile professional magazines for specialists were little popular and loss-making for their publishers. The comparatively small local market of the specialists resulted in the phenomenon that only the joint publications satisfying the needs of specialists in several related fields are financially worth publishing. Further, publishers of professional press still lack the support from the professional society.
Keywords: ...